Risk-Adapted Neoadjuvant Chemoradiotherapy in Rectal Cancer: Final Report of the OCUM Study - Ruppert, Reinhard; Junginger, Theodor; Kube, Rainer; Strassburg, Joachim; Lewin, Andreas; Baral, Joerg; Maurer, Christoph A.; Sauer, Joerg; Lauscher, Johannes; Winde, Guenther; Thomasmeyer, Rena; Stelzner, Sigmar; et al. (Journal of Clinical Oncology, 2023)
PURPOSEWe investigated whether neoadjuvant chemoradiotherapy (nCRT) in patients with rectal cancer can be restricted to those at high risk of locoregional recurrence (LR) without compromising oncological outcomes.PATIENTS AND METHODSIn a prospective multicenter interventional study, patients with rectal cancer (cT2-4, any cN, cM0) were classified according to the minimal distance between the tumor, suspicious lymph nodes or tumor deposits, and mesorectal fascia (mrMRF). Patients with a distance >1 mm underwent up-front total mesorectal excision (TME; low-risk group), whereas those with a distance a‰ 1 mm and/or cT4 and cT3 tumors in the lower rectal third received nCRT followed by TME surgery (high-risk group). The primary end point was 5-year LR rate.RESULTSOf the 1,099 patients included, 884 (80.4%) were treated according to the protocol. A total of 530 patients (60%) underwent up-front surgery, and 354 (40%) had nCRT followed by surgery. Kaplan-Meier analyses revealed 5-year LR rates of 4.1% (95% CI, 2.7 to 5.5) for patients treated per protocol, 2.9% (95% CI, 1.3 to 4.5) after up-front surgery, and 5.7% (95% CI, 3.2 to 8.2) after nCRT followed by surgery. The 5-year rate of distant metastases was 15.9% (95% CI, 12.6 to 19.2) and 30.5% (95% CI, 25.4 to 35.6), respectively. In a subgroup analysis of 570 patients with lower and middle rectal third cII and cIII tumors, 257 (45.1%) were at low-risk. The 5-year LR rate in this group was 3.8% (95% CI, 1.4 to 6.2) after up-front surgery. In 271 high-risk patients (involved mrMRF and/or cT4), the 5-year rate of LR was 5.9% (95% CI, 3.0 to 8.8) and of metastases 34.5% (95% CI, 28.6 to 40.4); disease-free survival and overall survival were the worst.CONCLUSIONThe findings support the avoidance of nCRT in low-risk patients and suggest that in high-risk patients, neoadjuvant therapy should be intensified to improve prognosis. ;copy; American Society of Clinical Oncology.
CRIS-Team Scopus Importer:2023-09-15